PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, BUDAYAORGANISASI, DAN KOMPETENSI PEDAGOGIK TERHADAPKINERJA GURU DI MTSN KERINCI - Arial Yulanda; Ali Idrus; Agus Lestari (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the influence of principal leadership,organizational culture, and pedagogical competence on teacher performance at MTsNKerinci.Methods: This study used a quantitative approach with a survey method. Thepopulation consisted of teachers at MTsN Kerinci. Data were collected throughquestionnaires and analyzed using multiple linear regression analysis to determine thepartial and simultaneous effects of the independent variables on teacher performance.Results: The results showed that principal leadership, organizational culture, andpedagogical competence had a positive and significant effect on teacher performanceboth partially and simultaneously. Effective school leadership, a positiveorganizational culture, and strong pedagogical competence contribute to improvingteachers’ professionalism and teaching effectiveness.Novelty: This study provides anintegrative perspective by combining managerial, cultural, and professional factors inone research model within the context of Islamic junior high schools (madrasah),which has unique organizational and spiritual characteristics compared to generalschools.Keywords: principal leadership, organizational culture, pedagogicalcompetence, teacher performance, madrasah